Opioid-free anesthesia in enhanced recovery after surgery for gastrointestinal surgery: current status, challenges, and prospects - Xu, Yongxing; Zhong, Maolin; Li, Shihong (Frontiers in Pharmacology, 2025)
The enhanced recovery after surgery (ERAS) protocol has been increasing implementation in gastrointestinal surgeries to optimize perioperative management, mitigate surgical stress responses, and accelerate patient recovery. Although opioid-based anesthesia effectively alleviates pain, it is associated with significant adverse effects, including postoperative nausea and vomiting (PONV), respiratory depression, and intestinal paralysis, which can impeder early recovery. Opioid-free anesthesia (OFA) is designed to alleviate these concerns. This article examines the pharmacological agents and regional block techniques commonly employed in OFA, emphasizing its role in promoting the recovery of gastrointestinal function, improving pain management, reducing adverse events, and enhancing patient satisfaction.